Mind the gap: brain-behaviour barriers to successful weight loss maintenance - Hume, David John (MRC/UCT RU for Exercise and Sport Medicine, 2016)
The primary objectives of this dissertation were to investigate the behavioural and neurophysiological factors related to overweight and obesity, as well as to weight loss maintenance versus weight relapse in a purposively sampled group of healthy South African women. The battery of investigations was designed to explore two central hypotheses: First, weight loss induces several behavioural compensations related to habitual eating behaviour and daily physical activity (PA) practices which facilitate the generation of a chronic positive energy balance, thereby increasing the risk of weight regain in reduced-overweight and reduced-obese women. Second, overweight and obese women as well as those at risk of undergoing relapse exhibit heightened indices of visual food cue-reactivity in various regions of the brain associated with obesogenic eating and reward-seeking tendencies. The novelty of this thesis lies in that we ascertained dietary, PA and psychobehavioural variables through both subjective accounts and objective measurement. Moreover, we employed electroencephalography to objectively evaluate high resolution temporal changes in visual food cue processing to test our second hypothesis. Overweight and obesity treatments focus, for the most part, on dietary- and/or exercise-centred interventions to facilitate weight loss. Our data suggest that certain interaction effects exist between the perception of environmental food cues and variables such as dietary restraint, habitual fat intake, body shape dissatisfaction and total body adiposity [Note: this thesis is embargoed until 30 November 2016]